Improving Students' Critical Thinking Skills in Mathematics with The CTL Approach - Jannah, Dakholatil; Tobroni, Tobroni; Andriani Kumala Dewi, Ririn (MASI Mandiri Edukasi, 2024)
The low results of students' critical thinking skills in mathematics subjects with the CTL approach at MI Uswatun Hasanah Jagapura Kulon on Fraction material. This study aims to determine how to apply the CTL approach in improving students' critical thinking skills in mathematics subjects at MI Uswatun Hasanah Jagapura Kulon and improve students’ critical thinking abilities in the field of mathematics subjects with the CTL approach at MI Uswatun Hasanah Jagapura Kulon. This research is a class action research conducted in 2 cycles, and the research subjects are students of class III-A MI Uswatun Hasanah Jagapura Kulon, which amounted to 21 students. Test results and observations obtained data on critical thinking skills in math lessons with the CTL approach. CTL contextual learning steps include constructivism, inquiry, questioning, learning community, modeling, reflection, and authentic assessment. The results showed a significant increase from pre-cycle to Cycle II, with the percentage of completeness increasing from 19.04% to 85.71%, showing an increase in the criteria for critical thinking skills from